Assessing the Realization of Speech Acts in the Conversation Section of â€œInteractive English 1â€ Textbook - Millatuz Zulfa; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2023)
Understanding speech acts and their functions is crucial for effective communication. Therefore, conducting research on the speech acts in English textbooks holds significant importance as it enables educators and curriculum designers to gain valuable insights into how language is used in real-life interactions. This study aimed to assess the speech acts realization in the English textbook entitled